Pengaruh Variasi Arus Pengelasan Gas Metal Arc Welding (GWAM) Terhadap Sifat Mekanis Pada Sifat Seamless - Gracia Irene Huka; Leslie. S. Loppies; Josef Matheus; Auliana Diah Wilujeng; Abdul Hamid (Journal Mechanical Engineering, 2023)
GMAW welding is a metal joining process with a melting process with the addition of a coil of wire in the form of electrodes and protective gas. Seamlees pipe, also known as seamless pipe, is an iron pipe without a connection. This study aims to produce data from the results of bending and impact testing on seamlees pipes by varying the welding current with a current of 21.5 volts, 22.5 volts, and 23.5 volts in GMAW welding. After the seamless pipe is welded, impact and bending tests are carried out on the seamlees pipe. From the bending/bending strength test, the highest flexural strength occurred at a current of 21.5 and 22.5 volts, while the lowest flexural strength occurred at a current of 23.5 volts. From the impact test, the highest strength occurred at 21.5 and 22.5 volts and the lowest was at 23.5 volts. Â Keywords: Seamlees pipe, GMAW welder, Bending Strength, Impact Strength. Â